(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the semantic and linguosemiotic features of proverbs used in Muhammad Sharif Gulxaniy’s Zarbulmasal. The study examines the symbolic meanings, metaphorical and metonymic structures, ironic expressions, and context-dependent semantic changes of proverbs in the work. Special attention is paid to the role of proverbs in revealing the ideological content and artistic-aesthetic value of the text. The article also studies the connection between folklore and literary discourse, as well as the functional-semantic role of paremias in the narrative structure. The research is based on comparative-semantic, contextual, and linguosemiotic analysis methods. It is established that the proverbs in “Zarbulmasal” function not only as elements of folk wisdom but also as important artistic devices expressing social criticism, moral values, and symbolic meanings. The article demonstrates that Gulxaniy skillfully used folk proverbs to expose social contradictions and enrich literary language.